2021
DOI: 10.1038/s41598-021-90489-9
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary rapid identification of pathogenic and antagonistic microorganisms associated with Coptis chinensis root rot by high-throughput sequencing

Abstract: Root rot reduces the yield and medical quality of C. chinensis (Cc). Previous studies of Coptis root rot focused on the identification of pathogens and the rhizosphere microbial community composition. The present study aimed to identify potential pathogenic and antagonistic microorganisms associated with root rot based on a high-throughput sequencing technique to prevent this disease. Healthy and diseased Cc in the endosphere and rhizosphere from the same field were collected to investigate the differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
2
8
0
Order By: Relevance
“…The results of the present study showed that Diaporthe eres , Fusarium avenaceum , and Fusarium solani were the dominant pathogens in the rhizosphere microbial community to cause root rot in C. chinensis . Among them, Fusarium avenaceum and Fusarium solani were consistent with the previous study's findings that both were pathogens closely related to C. chinensis root rot ( 11 ). And different from previous studies, the present study found that the abundance of Fusarium solani in healthy and diseased Coptis rhizosphere soils was significantly lower than that of Fusarium avenaceum .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results of the present study showed that Diaporthe eres , Fusarium avenaceum , and Fusarium solani were the dominant pathogens in the rhizosphere microbial community to cause root rot in C. chinensis . Among them, Fusarium avenaceum and Fusarium solani were consistent with the previous study's findings that both were pathogens closely related to C. chinensis root rot ( 11 ). And different from previous studies, the present study found that the abundance of Fusarium solani in healthy and diseased Coptis rhizosphere soils was significantly lower than that of Fusarium avenaceum .…”
Section: Discussionsupporting
confidence: 91%
“…However, similar to other tuberous medicinal plant, root rot is the main disease that harms the production and quality of C. chinensis . Previous studies have illustrated that plant metabolites and microflora contribute to host plant defense against pathogens ( 11 , 28 , 29 ). Recently, there has been increasing evidence that root/rhizosphere microbiota are directly or indirectly involved in host plant metabolic processes by regulating host secondary or specialized metabolism ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations